Geological carbon storage site characterization using a dual element seismic recording technology - Alireza Malehmir; Magdalena Markovic; Tanni Juul Abramovitz; Ulrik Gregersen (Scientific Reports)
Abstract Geologic carbon storage in saline acquirers is a feasible and scalable way of reducing atmospheric carbon dioxide (CO2). Since 2022, Denmark has stepped up site characterization at five suitable onshore locations for this purpose with a particular focus on four-way domal structures. A dual-element recording system incorporating landstreamer and wireless recorders was innovated and upscaled in a cost- and time-effective way for this purpose at the Rødby structure (one of the five sites). The dual-element recording allows a better imaging of the near-surface structures but also because of its broadband nature, it helps to retain higher resolution for imaging toplap structures and smaller faults in the area. The landstreamer data better image fault structures offsetting the Bunter Sandstone Formation, which is the primary reservoir, and the overlying geological seals such as Fjerritslev, Ørslev and Falster Formations. The Vedsted Formation, which a secondary seal in the region, appears unfaulted in the landstreamer data. The landstreamer data also reveal glacial valleys, near the surface, which are a source of groundwater. The two complementary datasets, from the landstreamer and nodal data, help to de-risk geological carbon storage in Denmark and is a solution we recommend to be adapted for onshore sites elsewhere in the world specially where the logistical acquisition challenges are not significant.